Effectiveness of cognitive analytic therapy for bipolar affective disorder: A co‐produced single subject cumulative treatment design with extended follow‐up (A1/B/A2/C‐FU). (10th March 2022) - Kellett, Stephen; Alhadeff, Lisa; Gaskell, Chris; Simmonds‐Buckley, Melanie
Abstract: Objectives: Evidence for the treatment of bipolar affective disorder with cognitive analytic therapy (CAT) is limited, and so this study sought to intensively evaluate outcomes in a co‐produced single‐case experimental design (SCED). Design: An A 1 /B/A 2 /C with extended follow‐up SCED with a female patient meeting diagnostic criteria for bipolar disorder. Methods: Following the 6‐week baseline period 'A 1 ', treatment occurred in two phases (18 'B' and 6 sessions 'C') sandwiching a 12‐week treatment withdrawal phase ('A 2 ') and a 24‐week structured follow‐up phase. Five idiographic daily measures were collected daily to create a 622‐day timeline. The PHQ‐9 and the Mania Rating Scale were completed after each treatment session. The participant held two roles: as the patient and provider of the idiographic/nomothetic outcomes and also as part of the research team through providing a commentary on the outcomes identified. Results: CAT was a partially effective intervention. There were improvements to idiographic measures of self‐criticism, self‐acceptance, body dissatisfaction and worry. Nomothetic outcomes showed little change. CAT did not insulate from the occurrence of a hypermanic relapse during the follow‐up phase. The change commentary mirrored the idiographic outcomes in noting that the 'exits' were harder to implement during the manic relapse. Conclusions: This co‐produced SCED suggests a partially effective CAT intervention, but with exits much harder to sustain during manic relapse. Methodologically, it is possible to improve SCED methodology through widening the participant role further beyond that of data collection.